(3GdHGYK Ydi GdNdGU ef MhGOK GdbUGUs - (3YHO GdQMje Hf GdMSjf Hf YHO GdQMef, CHh GdaVd, Rjf GdOjf, GdMGaX GdYQGbj, J (B806 (3g`s
(3ChdgG (B:s
(3bGd h QhjfG aj GdUMjMjf ef MOjK YGFTI QVj Gddg YfgG Cf QShd Gddg Udi Gddg Ydjg h Sde bGd (B:"(3ef CMOK aj CeQfG gPG eG djS efg agh QO (B" s
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B3 - (3U (B344 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B5 - (3U (B204s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B6 - (3U (B148 ; (3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B218s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJUha hGdBOGH GdTQYjIs